Risk factors for unavoidable removal of instrumentation after surgical site infection of spine surgery: A retrospective case-control study. Issue 43 (October 2016) - Tominaga, Hiroyuki; Setoguchi, Takao; Kawamura, Hideki; Kawamura, Ichiro; Nagano, Satoshi; Abematsu, Masahiko; Tanabe, Fumito; Ishidou, Yasuhiro; Yamamoto, Takuya; Komiya, Setsuro
Abstract : Abstract: Surgical site infection (SSI) after spine instrumentation is difficult to treat, and often requires removal of instrumentation. The removal of instrumentation after spine surgery is a severe complication that can lead to the deterioration of activities of daily living and poor prognosis. Although there are many reports on SSI after spine surgery, few reports have investigated the risk factors for the removal of instrumentation after spine surgery SSI. This study aimed to identify the risk factors for unavoidable removal of instrumentation after SSI of spine surgery. We retrospectively reviewed 511 patients who underwent spine surgery with instrumentation at Kagoshima University Hospital from January 2006 to December 2014. Risk factors associated with SSI were analyzed via multiple logistic regression analysis. Parameters of the group that needed instrumentation removal were compared with the group that did not require instrumentation removal using the Mann–Whitney U and Fisher's exact tests. The posterior approach was used in most cases (453 of 511 cases, 88.6%). SSI occurred in 16 of 511 cases (3.14%) of spine surgery with instrumentation. Multivariate logistic regression analysis identified 2 significant risk factors for SSI: operation time, and American Society of Anesthesiologists physical status classification ≥ 3. Twelve of the 16 patients with SSI (75%) were able to keep the instrumentation after SSI. Pseudarthrosis occurred in 2 of 4 cases (50%) after instrumentation removal. Risk factors identified for instrumentation removal after spine SSI were a greater number of past surgeries, low preoperative hemoglobin, high preoperative creatinine, high postoperative infection treatment score for the spine, and the presence of methicillin-resistant Staphylococcus aureus . In these high risk cases, attempts should be made to decrease the risk factors preoperatively, and careful postoperative monitoring should be conducted. Abstract : Supplemental Digital Content is available in the text